Conditioned consent in organ transplantation - Camacho, Miguel (1995)
The attitude of 184 family groups toward death and organ donation in encephalic death is analized. Seventy-seven per cent donations done between 1992 and 1995 had family condinioted consent. The family preferred to provide only the kidneys in order to avoid necropsy and keep the corpe's integrity. Furthermore, poverty of potential donors made the family to ask for economical support for hospitalization and burial. To avoid possible commercialization of of organs for transplantation, the family requested to identify recipients or to come into the operating room in order to make sure the destiny of donated organs. Unlike USA and Europe, Peru and maybe other developing countries have the special situation of conditioned consent in organs donation, necropsy denial and request for "compensation" for donation. Transparence in organ transplantation is the probable only alternative to commercialization of organs.